Chapter The Idea of Italian Travellers to Iran. Scholarly Research and Cultural Diplomacy in Post-war Italy - Giusti, Emanuele (Connessioni. Studies in Transcultural History, 2022)
This essay discusses the formation of "Italian travellers to Iran" as both a popular idea and scientific category. In the three decades after the Second World War, Italy and Iran were going through deep transformations and entered a phase of intense political, economic and cultural relations. In this context, scholarly interests and political agendas jointly contributed to a representation of past travellers as the manifestation of an imagined and almost eternal connection between the two civilizations. This narrative served to rhetorically enhance the role played by both countries in the history of mankind, and the contribution they could still give to humanity as nations among nations. However, these events may have also left their mark on how the history of connections between Italy and Iran, and the history of Iranian studies in Italy, are represented in scholarly milieus.